2017
DOI: 10.18632/oncotarget.17887
|View full text |Cite
|
Sign up to set email alerts
|

HPV-associated differential regulation of tumor metabolism in oropharyngeal head and neck cancer

Abstract: HPV-positive oropharyngeal cancer patients experience significantly lower locoregional recurrence and higher overall survival in comparison with HPV-negative patients, especially among those who received radiation therapy. The goal of the present study is to investigate the molecular mechanisms underlying the differential radiation sensitivity between HPV-negative and HPV-positive head and neck squamous cell carcinoma (HNSCC). Here, we show that HPV-negative HNSCC cells exhibit increased glucose metabolism as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 48 publications
2
42
1
Order By: Relevance
“…In HNSCC, an immunohistochemical analysis of patient samples found evidence of heightened mitochondrial respiration in proliferative tumor cells, which the authors found to be especially common in high-grade lesions 36 . A similar upregulation of mitochondrial respiration in HNSCC has been attributed to HPV positivity 37 . These findings implicate mitochondrial metabolism in the pathogenesis and progression of at least certain subsets of cancers, including HNSCC; if in part regulated by β2AR, as suggested by the data herein, this may represent a therapeutically targetable pathway.…”
Section: Discussionsupporting
confidence: 53%
“…In HNSCC, an immunohistochemical analysis of patient samples found evidence of heightened mitochondrial respiration in proliferative tumor cells, which the authors found to be especially common in high-grade lesions 36 . A similar upregulation of mitochondrial respiration in HNSCC has been attributed to HPV positivity 37 . These findings implicate mitochondrial metabolism in the pathogenesis and progression of at least certain subsets of cancers, including HNSCC; if in part regulated by β2AR, as suggested by the data herein, this may represent a therapeutically targetable pathway.…”
Section: Discussionsupporting
confidence: 53%
“…Also, high HIF-1α expression strongly correlated with high CA in HPV-neg OPSCCs. Previously, however, separate studies have reported conflicting results regarding HIF-1α expression in HPV-pos versus HPV-neg tumors [38,39]. Other endogenous hypoxia markers such as CA IX have also not yielded definitive results [40].…”
Section: Discussionmentioning
confidence: 99%
“…For the genotyping of the viral DNA, the Luminex platform was used for bead-based array. The EIA detected 14 HPV types: 16,18,31,33,35,39,45,51,52,56,58,59,66,68. β-globin PCR was used to test for sample quality post-DNA extraction [43].…”
Section: Hpv Analysismentioning
confidence: 99%
“…However, the relative hypoxic expression signal and absolute protein increase was higher in the HPV-positive cell lines. Recently, it has been shown that HIF-1α protein accumulates in HPV-positive and -negative HNSCC cell lines under hypoxia [ 24 ], but no elevated accumulation of HIF-1α protein levels in the HPV-positive cell lines was detected under normoxic conditions [ 25 ]. In accordance with our investigations, earlier studies have shown HIF-1α stabilization by HPV under hypoxic conditions (chemically induced) in HPV E6/E7 oncoprotein transfected cells or cervical cell lines [ 6 , 8 , 26 ].…”
Section: Discussionmentioning
confidence: 99%